Soil Preparation Studies: I. The Effect of Depth and Method of Soil Preparation and of Organic Material on the performance of Vi tis Vinifera (var. Chenin Blanc) on Hutton/Sterkspruit Soil - Saayman, D.; Van Huyssteen, L. (South African Journal of Enology and Viticulture, 2017)
The effect of depth and method of soil preparation and of organic material on the performance of a Chenin blanc/101-14 Mgt. vineyard, grown on a Hutton/Sterkspruit soil, was studied in the Robertson irrigation area. The apparent lack of response to depth of soil preparation was traced to soil variation and to the inability of the deep delving implement to work down to the desired depth. A general tendency, directly relating shoot growth and yield to soil depth, could be demonstrated. It appears that the high cost of soil preparation is justified, and that the delve plough was more efficient than a ripper. No technical benefit was obtained from the application of either straw or compost during soil preparation.